Limit behavior of an oscillating thin layer - Abdelaziz Ait Moussa (Electronic Journal of Differential Equations, 2006)
We study the limit behavior of a thermal problem, of a containing structure, an oscillating thin layer of thickness and conductivity depending of $varepsilon$. We use the the epi-convergence method to find the limit problems with interface conditions. The obtained results are tested numerically.